Analisis Psikologi Tokoh Keke dalam Novel Surat Kecil untuk Tuhan: Kajian Psikologi Sigmund Freud - Hikmatul Maghfiroh; Ahmad Izzamul Hikam (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
The purpose of this study is to analyze the psychological dynamics of the character Keke in the novel Surat Kecil Untuk Tuhan using the literary psychology approach developed by Sigmund Freud. The main focus of this study lies in the main aspects of personality possessed by humans that have been stated in the psychoanalytic theory approach of Sigmund Freud. These three approaches include the idea of ego and super ego, which in it represent the basic structure in the development of human personality. The results of this analysis indicate that the character Keke has a strong ID which is reflected through the instinctive drive to survive and avoid the suffering that comes from the cancer he has. The aspect of the elder brother's ego is seen from his rational attitude in facing the reality of life, such as in his decision to continue going to school and undergoing chemotherapy for his recovery. While the last aspect, namely the super ego, is stated to be more prominent than other aspects, the super ego aspect possessed by Keke stands out in the form of moral toughness, religious values and social responsibility, for example when he tells his family not to be sad and not to sacrifice all his wealth for the treatment of his illness. These three aspects of personality interact with each other and form a balanced personality between each other even though they are in a bad condition. Through the psychoanalytic approach of Sigmund Freud, the character of Keke in the novel Surat Kecil untuk Tuhan, the character of Keke is stated as a character who can inspire and has very high moral values. The analysis of this novel also proves that the psychoanalytic theory owned by Sigmund Freud is very effective in exploring the inner depths of a character and can understand the emotional and spiritual complexity in dealing with the suffering felt by a character in his story.